2016
DOI: 10.1002/kpm.1507
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Processes, Absorptive Capacity and Innovation: A Mediation Analysis

Abstract: The present research aims to explore the role of knowledge creation and absorptive capacity as mediating variables between knowledge acquisition, knowledge sharing, and companies' organizational innovation. A theoretical model supporting the hypothesized relationships is developed, and then research hypotheses are tested with a sample of 111 industrial organizations, using partial least squares structural equation modeling. The results show that knowledge creation positively influences innovation and partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 90 publications
(150 reference statements)
7
41
0
1
Order By: Relevance
“…These were in conformance to the current findings where knowledge sharing was found to have a significant and positive association with the innovation capability of an organization. This study was further in conformance with a previous study conducted by Costa and Monteiro (2016), who found out that knowledge sharing played a significant role in fostering innovation. Additionally, case studies conducted by Okuyama (2017) on two Japanese pharmaceutical companies also highlight that both explicit and tacit knowledge work in tandem for incremental innovation processes.…”
Section: Discussing the Findingssupporting
confidence: 91%
“…These were in conformance to the current findings where knowledge sharing was found to have a significant and positive association with the innovation capability of an organization. This study was further in conformance with a previous study conducted by Costa and Monteiro (2016), who found out that knowledge sharing played a significant role in fostering innovation. Additionally, case studies conducted by Okuyama (2017) on two Japanese pharmaceutical companies also highlight that both explicit and tacit knowledge work in tandem for incremental innovation processes.…”
Section: Discussing the Findingssupporting
confidence: 91%
“…The valuable knowledge can be sourced from both external and internal sources. Use of internal and external knowledge in an organized way can add value to the operational performance along with achievement of competitive advantage for the firm (Costa & Monteiro, 2016;Dahiyat, 2015). The results reveal that the innovation of process has a positive mediating influence on the relation of operational performance and KM.…”
Section: Resultsmentioning
confidence: 92%
“…It is assumed by the theory that resources are valuable, rate, imitable and non-substitutable. Moreover, the resources support in the achievement of competitive advantage (Bromiley & Rau, 2016;Costa & Monteiro, 2016;Dahiyat, 2015). It has been argued that manufacturing companies become able to innovation through KM capability, which improves the operational performance of an organization.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations